Concepções de estágio e de formação docente no Brasil após a 'Constituição Cidadã' de 1988 - Bassiquette, Silvia Cristina Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The education is relevant to the citizenship formation of any individual, which corresponds to the personal and professional construction, whose values, principles, ideas, ideals and daily actions make influence on the social question. Brazil has presented problems of critical order critical in a high expressiveness, which conduces to understanding the basis of education that consists in analyzing the historical course of its development with emphasis on the supervised stage and teacher training. Such reality made possible to structure this study, which had the purpose to identify the conceptions related to the teacher training, being more specifically on the supervised internships, as well as their structuring from a legal point of view in addition to teacher training, aiming to point the corroboration of these legal provisions in the process of school insertion. In order to do so through a literary review, it became possible to note that even in the face of the several laws that propose a pedagogical model focused on teacher training with a supervised stage, this is not yet ideally tangible. Results made possible to percept that there is a systematization under development, which is of expressive importance to the construction of the future professional of the sector

Considerando a relevância da educação na formação cidadã de um indivíduo, o que condiz com sua construção pessoal e profissional, cujos valores, princípios, ideias, ideais e ações cotidianas influenciam na sua questão social, e que no Brasil tem apresentado problemas de ordem crítica de alta expressividade, compreender a base da educação consiste em analisar o percurso histórico do desenvolvimento da educação com ênfase no estágio supervisionado e na formação docente. Deste modo, este estudo objetivou identificar as concepções relativas à formação docente, mais especificamente sobre os estágios supervisionados, bem como sua estruturação do ponto de vista legal, em adendo à formação docente, visando apontar a corroboração destas disposições legais no processo de inserção escolar. Para tanto, por meio de uma revisão literária, se fez possível notar que mesmo diante das inúmeras leis que propõem um modelo pedagógico focado na formação docente com estágio supervisionado, isso ainda não é tangível de modo ideal. Viuse que há uma sistematização em desenvolvimento, sendo esta de supra importância à construção do futuro profissional do setor
Keywords: Estagios supervisionados; Professores - Formação; Educação; Pesquisa bibliografica; Brasil